The Deaths of Sisyphus: Structural Analysis of a Classical Myth - Raffalovic, Daniel C. (Anthropologica, 2022)
As punishment for deceiving death, Sisyphus must end lessly roll a rock up a hill in Hades, only for it to roll back down. A structural analysis reveals the connections between the punishment and the crime, and demonstrates that the interpretation of myth resides in the operations of thought, not in particular contents.